(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This study compares traditional and online learning from three angles in order to highlight thedivergent views. To begin, a study of the existing literature on both traditional and online education willbe conducted. This study will look at the attitudes of management students towards traditional andonline learning. Thirdly, they’ll research the differences between traditional and online education andhow they affect students’ academic performance. The effects of globalization on management educationin India have been positive. The obsolete conventional methods of teaching are being replaced by thenew era of technology-enabled education, or ’e-learning.’ Online learning and m-learning are twodifferent but related terms. When it comes to the distinctiveness of online learning, it allows students tolearn at any time, from any location. Instead than allowing advanced students to skip or rush throughtraining that is repetitive, teachers instead encourage students to take their time and study at their ownpace, thereby removing any potential roadblocks.